Coupling Metallic Nanostructures to Thermally Responsive Polymers Allows the Development of Intelligent Responsive Membranes - J. Rubén Morones-Ramírez (International Journal of Polymer Science)
Development of porous membranes capable of controlling flow or changing their permeability to specific chemical entities, in response to small changes in environmental stimuli, is an area of appealing research, since these membranes present a wide variety of applications. The synthesis of these membranes has been mainly approached through grafting of environmentally responsive polymers to the surface walls of polymeric porous membranes. This synergizes the chemical stability and mechanical strength of the polymer membrane with the fast response times of the bonded polymer chains. Therefore, different composite membranes capable of changing their effective pore size with environmental triggers have been developed. A recent interest has been the development of porous membranes responsive to light, since these can achieve rapid, remote, noninvasive, and localized flow control. This work describes the synthesis pathway to construct intelligent optothermally responsive membranes. The method followed involved the grafting of optothermally responsive polymer-metal nanoparticle nanocomposites to polycarbonate track-etched porous membranes (PCTEPMs). The nanoparticles coupled to the polymer grafts serve as the optothermal energy converters to achieve optical switching of the pores. The results of the paper show that grafting of the polymer and in situ synthesis of the metallic particles can be easily achieved. In addition, the composite membranes allow fast and reversible switching of the pores using both light and heat permitting control of fluid flow.